Various paradigms in the social work area and it typical assistance institutions (Psicologia USP, 2012)
In order to understand what is the situation of entities that serve children and adolescents today, as well as the institutional plot that comprises these institutions, we aimed to formulate a set of paradigmatic possibilities that would allow us to understand the configuration of the dialectical field of various pulses, in which these entities are located. We detected the subjects we associate with counterparts paradigms of Charity, of Human Promotion, of Philanthropy, of assistentialist government patronage, of Social Work as a State Policy, and finally, another set of events that we propose to designate as the paradigm of Citizen Subjects we associate with the ethical perspective of People Education. These paradigmatic possibilities range from the simply various and contrasting ones, including the similar and competing ones, to the dialectically contradictory ones. Its spectrum oscillates between tutelage and citizenship. The characterization of these didactic paradigms can provide us a compass that is required in a highly complex social field, allowing us to understand the variety of ethical effects promoted by these paradigms in the social field.